1.(a+b+c)^3-(a+b+c)^3-(a-b+c)^3-(-a+b+c)^3
2)x^3+ax^2-7x-10
3)(x^2+x)^2-(x^2+x)+15
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: \(x^3+3x^2-x-3=\left(x-2\right)\left(x^2+bx+c\right)+a\)
\(\Leftrightarrow x^3-2x^2+5x^2-10x+11x-22+19=\left(x-2\right)\left(x^2+bx+c\right)+a\)
\(\Leftrightarrow\left(x-2\right)\left(x^2+5x+11\right)+19=\left(x-2\right)\left(x^2+bx+c\right)+a\)
=>b=5; c=11; c=19
2: \(4x^3+7x-6=\left(ax+b\right)\left(x^2+x+1\right)+c\)
\(\Leftrightarrow4x^3+4x^2+4x-4x^2-4x-4+7x-2=\left(ax+b\right)\left(x^2+x+1\right)+c\)
\(\Leftrightarrow\left(x^2+x+1\right)\left(4x-4\right)+7x-2=\left(ax+b\right)\left(x^2+x+1\right)+c\)
=>a=4; b=-4; c=7x-2
`@` `\text {Ans}`
`\downarrow`
`B(x)-A(x)+C(x)`
`=`\((x^2-5x^3-4x+7) - (-x^3 + 7x^2 +2x - 15) + 3x^3 - 7x^2 -4\)
`=`\(x^2-5x^3-4x+7+x^3-7x^2-2x+15+3x^3-7x^2-4\)
`=`\(\left(-5x^3+x^3+3x^3\right)+\left(x^2-7x^2-7x^2\right)+\left(-4x-2x\right)+\left(7+15-4\right)\)
`=`\(-x^3-13x^2-6x+18\)
`C(x)-B(x)-A(x)`
`=`\(3x^3 - 7x^2 -4 - (x^2-5x^3-4x+7) - (-x^3 + 7x^2 +2x - 15)\)
`=`\(3x^3-7x^2-4-x^2+5x^3+4x-7+x^3-7x^2-2x+15\)
`=`\(\left(3x^3+5x^3+x^3\right)+\left(-7x^2-x^2-7x^2\right)+\left(4x-2x\right)+\left(-4-7+15\right)\)
`=`\(9x^3-15x^2+2x+4\)
a) \(B\left(x\right)-A\left(x\right)+C\left(x\right)\)
\(=\left(x^2-5x^3-4x+7\right)-\left(-x^3+7x^2+2x-15\right)+\left(3x^3-7x^2-4\right)\)
\(=x^2-5x^3-4x+7+x^3-7x^2-2x+15+3x^3-7x^2-4\)
\(=\left(-5x^3+x^3+3x^3\right)+\left(x^2-7x^2-7x^2\right)-\left(4x+2x\right)+\left(7-4+15\right)\)
\(=-x^3-13x^2-6x+18\)
b) \(C\left(x\right)-B\left(x\right)-A\left(x\right)\)
\(=\left(3x^3-7x^2-4\right)-\left(x^2-5x^3-4x+7\right)-\left(-x^3+7x^2+2x-15\right)\)
\(=3x^3-7x^2-4-x^2+5x^3+4x-7+x^3-7x^2-2x+15\)
\(=\left(3x^3+5x^3+x^3\right)-\left(7x^2+x^2+7x^2\right)+\left(4x-2x\right)-\left(4+7-15\right)\)
\(=9x^3-15x^2+2x+4\)
\(1,\\ a,=-35x^5y^4z\\ b,=6x^2-30x-6x^2-3x=-33x\\ c,=x^3-9x^2-2x^2+18x-x+9=x^3-11x^2+17x+9\\ 2,\\ A\left(x\right)+B\left(x\right)=10-2x+4x^3-5x^2-10x^3-5x+6x^2-20\\ =-6x^3+x^2-7x-10\\ A\left(x\right)-B\left(x\right)=10-2x+4x^3-5x^2+10x^3+5x-6x^2+20\\ =14x^3-11x^2+3x+30\\ 3,\\ a,M\left(x\right)=5x+20=0\\ \Leftrightarrow x=-4\\ b,N\left(x\right)=100x^2-49=0\\ \Leftrightarrow\left(10x-7\right)\left(10x+7\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=\dfrac{7}{10}\\x=-\dfrac{7}{10}\end{matrix}\right.\\ c,P\left(x\right)=3x-15=0\\ \Leftrightarrow x=5\)
Bài 1;
a)\(5x^3yz.\left(-7x^2y^3\right)=-35.x^5y^4z\)
b)\(6x\left(x-5\right)-x\left(6x+3\right)=6x^2-30x-6x^2-3x=-33x\)
c) \(\left(x-9\right)\left(x^2-2x-1\right)=x^3-2x^2-x-9x^2+18x+9=x^3-11x^2+17x+9\)
câu 2 là: x^3+4x^2-7x-10 nhà, mk ghi lộn, xl các bn
Câu 2:
\(x^3+4x^2-7x-10\)
\(=x^3+5x^2-x^2-5x-2x-10\)
\(=\left(x+5\right)\left(x^2-x-2\right)\)
\(=\left(x+5\right)\left(x-2\right)\left(x+1\right)\)